2023
DOI: 10.1038/s41598-023-33062-w
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of cell free supernatants from probiotics inhibits against pathogenic bacteria isolated from fresh boar semen

Abstract: The use of antibiotics with semen extender appears to be a practical solution to minimise bacterial growth in fresh boar semen preservation. Unfortunately, the excessive use of antibiotics promotes antimicrobial resistance (AMR). This becomes a worldwide concern due to the antimicrobial resistance genes transmitted to animals, environment, and humans. Probiotics are one of the alternative methods to reduce antibiotic use. They could inhibit pathogenic bacteria by producing antimicrobial substances in cell free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The bacteria in the present study were obtained from our previous report by Keeratikunakorn et al [7] in which three species of the most frequently found bacteria in fresh boar semen including E. coli, Pseudomonas aeruginosa, and Proteus mirabilis were isolated and kept in a culture collection at the Laboratory of Bacteria, Veterinary Diagnostic Center, Faculty of Veterinary Science, Mahidol University (Salaya, Phuttamonthon, Nakhon Pathom, Thailand). The bacteria E. coli, Pseudomonas aeruginosa, and Proteus mirabilis were all grown in a brain heart infusion (BHI, Difco, Reno, NV, USA) medium and incubated for 16-18 h at 37 • C. Pre-culture was performed by inoculating BHI broth with a single isolated colony and then shaking it at 200 rpm for 16-18 h at 37 • C. Before being used, a 1% concentration of the pre-culture was added to the BHI broth and kept to grow at 37 • C.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…The bacteria in the present study were obtained from our previous report by Keeratikunakorn et al [7] in which three species of the most frequently found bacteria in fresh boar semen including E. coli, Pseudomonas aeruginosa, and Proteus mirabilis were isolated and kept in a culture collection at the Laboratory of Bacteria, Veterinary Diagnostic Center, Faculty of Veterinary Science, Mahidol University (Salaya, Phuttamonthon, Nakhon Pathom, Thailand). The bacteria E. coli, Pseudomonas aeruginosa, and Proteus mirabilis were all grown in a brain heart infusion (BHI, Difco, Reno, NV, USA) medium and incubated for 16-18 h at 37 • C. Pre-culture was performed by inoculating BHI broth with a single isolated colony and then shaking it at 200 rpm for 16-18 h at 37 • C. Before being used, a 1% concentration of the pre-culture was added to the BHI broth and kept to grow at 37 • C.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…A rectal swab sample of diarrheal piglets revealed 100% resistance of E. coli to amoxicillin, and 97.3% of these bacteria exhibited multidrug resistance (MDR) [3]. Antibiotic-resistant genes have also been identified, including those from E. coli collected from diarrheal piglets and boar semen (int1, mcr-1 and mcr-3) [3,6]. It has been shown that among the bacteria isolated from sows with endometritis and those showing vaginal discharge (i.e., E. coli, Staphylococcus spp., and Streptococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…This particular AMP showed a compromised result in terms of inhibiting Gram-negative bacteria with MDR. According to studies at pig farms in tropical countries, bacteria in boar semen are resistant to multiple antibiotics, such as amoxicillin, gentamicin, and colistin, commonly used in pig farms and supplemented in the boar semen extender [6,15]. It has also been demonstrated that E. coli isolated from boar semen has a unique MDR pattern [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals prone to recurrent infections often face persistent concerns, as antibiotic therapy is frequently ineffective due to drug resistance. Several probiotic strains, tested in a growing number of trials, have demonstrated promising effects in preventing or treating both acute and recurring infectious diseases (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%